Impact of BMI on HER2+ metastatic breast cancer patients treated with pertuzumab and/or trastuzumab emtansine. Real‐world evidence. Issue 11 (15th January 2020) - Krasniqi, Eriseld; Pizzuti, Laura; Barchiesi, Giacomo; Sergi, Domenico; Carpano, Silvia; Botti, Claudio; Kayal, Ramy; Sanguineti, Giuseppe; Marchetti, Paolo; Botticelli, Andrea; Marinelli, Daniele; Gamucci, Teresa; et al.
Abstract: Body mass index (BMI) is a main indicator of obesity and its association with breast cancer is well established. However, little is known in the metastatic setting, especially in HER2‐positive patients. We assessed the influence of BMI on clinical outcomes of patients treated with pertuzumab and/or trastuzumab emtansine (T‐DM1) for HER2+ metastatic breast cancer (mBC). BMI was addressed as a categorical variable, being classified on the basis of the following ranges, that is, 18.5–24.9, 25–29.9, and 30.0–34.9, namely, normal weight, overweight, and Class I obesity. The outcomes chosen were progression‐free survival to first‐line chemotherapy (PFS1) and overall survival (OS). Overall ( N  = 709), no impact of BMI was observed on PFS1 ( p  = .15), while BMI ≥ 30 was associated with worse OS ( p  = .003). In subjects who progressed to first line ( N  = 575), analyzing data across PFS1 quartiles and strata of disease burden, BMI predicted lower PFS1 in patients within the I PFS1 quartile and with the lowest disease burden ( p  = .001). Univariate analysis showed a detrimental effect of BMI ≥ 30 on OS for women within the I PFS1 quartile ( p  = .03). Results were confirmed in multivariate analysis. According to PFS1 quartiles a higher percentage of patients with high BMI and low disease burden progressed within 6 months of therapy. The effect of BMI on prognosis was also confirmed in multivariate analysis of OS for overall population. In our cohort, a BMI ≥ 30 correlated with worse OS in patients with HER2+ mBC who received pertuzumab and/or T‐DM1 but had no impact on PFS to first line. BMI predicted worse I PFS1 quartile. Abstract : We found that a body mass index ≥ 30 correlates with worse overall survival in HER2+ metastatic breast cancer patients treated with pertuzumab and/or trastuzumab emtansine but had no impact on progression‐free survival (PFS) to first line. BMI predicted worse I PFS1 quartile.